Hoạt động Tân kiến tạo và ảnh hưởng của chúng đến nứt, sụt đất khu vực Thanh Ba - Phú Thọ - Thơm, Bùi Văn; Huyên, Nguyễn Xuân (Vietnam Journal of Earth Sciences, 2012)
Summary Neotonic activities and their effects to land-rupture hazards in Thanh Ba region, Phu Tho Province In Neotectonic periods, the Thanh Ba region consists of three main tectono-structural blocks : the Northeastern block, the Central block and the Southwestern block, consisting of many active faults (mainly oriented to northeast - southwest). Activity of the active structures is one of the direct causes of ground faulting (in Yen Noi, Hanh Cu communes), and indirect causes of land subsiding (in Ninh Dan, Dong Xuan and Yen Noi communes) through formation and development of crushed - fractured rock zones and fissure crack systems that have two main orientations : northeast - southwest and sub-longtitudial along the faults and between structural boundaries. These factors cause favourable conditions for migration and concentration of ground-water and speed up ground karstification in carbonate formation. Studied results determined four regions that have high risk about land subsidence hazards : area 2, 3, 4 and 6 in Ninh Dan ; area 3 in Yen Noi ; and area 3 and 4 in Dong Xuan, all locating on northeastern - southwestern basin (belong to the Central block).